2023
DOI: 10.1002/cphc.202200780
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Hydrogen Bonding Donor (HBD) Parameters of Organic Solvents Using Solvatochromic Probes – A Critical Evaluation

Abstract: The solvatochromicity of established solvatochromic UV/Vis probes, which appear to be sensitive to the so-called hydrogen bond donor (HBD) property of the solvent, is analysed using the hydroxyl group density of alcoholic solvents D HBD as a physical parameter in comparison to the pKa, the chemical benchmark for acidity. Reichardt's dye B30, Kosowers Z-indicator 1-ethyl-4-(methoxycarbonyl) pyridinium iodide (K), Kamlet-Tafts α, Dragos S parameter, Catalans SA scale, the cis-dicyano-bis (1,10phenanthroline) iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 200 publications
1
14
0
Order By: Relevance
“…The collections of polarity scales developed by Catalán and Kamlet–Abboud–Taft (KAT) are widely utilized in this field. The overall suitability of these two techniques has been the subject of a current dispute. A new version of the KAT model, known as m -KAT, was proposed in response, and the solvent acidity terms in these models were subjected to critical evaluation . Recently, we have shown that Catalán’s collection of solvent polarity scales is more effective than the original KAT collection in identifying the important solvent properties that contribute to the observed solvatochromism in a series of organic sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collections of polarity scales developed by Catalán and Kamlet–Abboud–Taft (KAT) are widely utilized in this field. The overall suitability of these two techniques has been the subject of a current dispute. A new version of the KAT model, known as m -KAT, was proposed in response, and the solvent acidity terms in these models were subjected to critical evaluation . Recently, we have shown that Catalán’s collection of solvent polarity scales is more effective than the original KAT collection in identifying the important solvent properties that contribute to the observed solvatochromism in a series of organic sensors.…”
Section: Resultsmentioning
confidence: 99%
“…24−26 A new version of the KAT model, known as m-KAT, 24 was proposed in response, and the solvent acidity terms in these models were subjected to critical evaluation. 27 Recently, we have shown that Catalań's collection of solvent polarity scales is more effective than the original KAT collection in identifying the important solvent properties that contribute to the observed solvatochromism in a series of organic sensors. This shows that Catalań's collection is suitable for establishing relationships between the structure of the sensors and their solvatochromic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…41,42 Recently, a revision of the KAT model have been proposed, 43 and Spange et al have carried out a critical evaluation of the terms related to solvent acidity of these models. 44 We recently illustrated the superiority of Catalán's solvent polarity scales collection over the original KAT collection in determining the significant solvent property contributions to the solvatochromism observed for a series of organic sensors and showing its suitability for establishing some structure–solvatochromic behavior relationships. 23,45 Therefore, the solute–solvent interactions responsible for the inverted solvatochromism of dyes 3–6 were quantified using a multiparametric regression analysis with eqn (1) and the Catalan's scales for solvent hydrogen-bond donor (HBD) acidity (SA), hydrogen-bond acceptor (HBA) basicity (SB), solvent polarizability (SP), and solvent dipolarity (SdP). E T = E 0 T + a SA + b SB + c SP + d SdP…”
Section: Resultsmentioning
confidence: 99%
“…An actual preferential solvation could be demonstrated for B30 in the phenol/acetone and phenol/acetonitrile systems [43,44]. A stoichiometric 1:1 complex of B30 with phenol can be clearly identified.…”
Section: Introductionmentioning
confidence: 83%
“…The interaction of the solvent HBD groups with the phenolate oxygen was considered to be critical in measuring the Liquids 2024, 4 192 HBD strength of solvents and solvent mixtures. However, this approach is only partially justified, as we have recently shown [43]. The concept of determining HBD parameters works quite well for ionic liquids (ILs) and other salts due to the electrostatic interaction between the B30 phenolate anion and the constituent cation of the IL [41,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%